Internalization of Economic Education for Subak Farmers - Kertiasih, Luh; Kusumojanto, Djoko Dwi; Churiyah, Madziatul (LPPM Undiksha, 2021)
This study aims to examine the internalization of economic education for subak farmers. This study uses a qualitative approach and the type of phenomenological research. Sources of data in this study are primary sources and secondary sources. The primary sources in the study were headman and subak farmers. Secondary sources in this research are documents related to research. The population in this study was 68 subak. The results of this study are Balinese cultural values consisting of religious values, happiness values, togetherness values, family values, and austerity values that underlie economic behavior of rationality, morality, and altruism. The form of internalization of economic education for subak farmers is economic education learning through (1) exemplary parents to their children in production, consumption, and distribution activities, (2) verbal explanations from parents to their children regarding economic activities, managing finances, economic management strategies, economic themes, (3) Discussion of relevant cases regarding expressing opinions and making decisions, family economic problems, and careful use of money. The obstacles to internalizing economic education for subak farmers are internal and external constraints.